Modeling and measurement of influence of mechanical prestress on hysteresis of ferroelectric actuators - Wolf, Felix; Sutor, Alexander; Rupitsch, Stefan; Lerch, Reinhard (Procedia Engineering, 2011)
In various ferroelectric actuator applications, the active material is exposed to mechanical prestress. This is often caused by unintended clamping, such as for smart materials with embedded ferroelectric components. In other cases, the stress is applied on purpose to enhance the transducer performance or to prevent from tensile forces. Hence, the development of models, describing the transducer behavior under combined, electro-mechanical loading conditions is essential. In our previous work, we proposed an analytic weight function for the scalar Preisach hysteresis operator. The model was further enhanced to describe the dynamic material behavior of piezoceramic actuators. Here, we address the influence of uniaxial mechanical prestress on the polarization hysteresis by conducting measurements on lead zirconate titanate samples. A parameter study is performed to investigate, how the weight function can be extended to a formulation incorporating prestress. The resulting simulations coincide very well with measurements. (C) 2011 Published by Elsevier Ltd.
Keywords: Preisach model; analytic weight function; uniaxial compressive prestress; piezoelectric transducer; piezoceramic actuator; ferroelectric hysteresis; PZT